If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3(t + -7) + -1(t + 9) = 9 Reorder the terms: -3(-7 + t) + -1(t + 9) = 9 (-7 * -3 + t * -3) + -1(t + 9) = 9 (21 + -3t) + -1(t + 9) = 9 Reorder the terms: 21 + -3t + -1(9 + t) = 9 21 + -3t + (9 * -1 + t * -1) = 9 21 + -3t + (-9 + -1t) = 9 Reorder the terms: 21 + -9 + -3t + -1t = 9 Combine like terms: 21 + -9 = 12 12 + -3t + -1t = 9 Combine like terms: -3t + -1t = -4t 12 + -4t = 9 Solving 12 + -4t = 9 Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-12' to each side of the equation. 12 + -12 + -4t = 9 + -12 Combine like terms: 12 + -12 = 0 0 + -4t = 9 + -12 -4t = 9 + -12 Combine like terms: 9 + -12 = -3 -4t = -3 Divide each side by '-4'. t = 0.75 Simplifying t = 0.75
| -23+w=48 | | 4x^2+4y^2-72=0 | | 3(b+6)=360 | | 10*21= | | 2x^3+3x^2-12x=0 | | 10x^2+6+2x=0 | | 7x+9-x-4= | | 10x-3=x+15 | | -7b=-84 | | 15+a=-8 | | 9+9c=0 | | y=.125x+12 | | a-3=-19 | | 10t+211=235 | | 5n-2m+3n+n= | | 5+3p=83j | | -10=m-6 | | 92+x=92 | | 15=3-6x | | 4(3x+1)-6x=7x+5 | | 10x^2+19xy-15y^2=0 | | X^2=10x+17 | | 3x+2(x+1)=4(x+5) | | x+10=7x-8 | | x+x*2+x*3=405 | | graphy=2x+6 | | 1.8*16=t | | 30k^2+38k+12=0 | | T=1.8*16 | | 30k^2+38k+121=0 | | 11x-2=-22 | | b^2+12b=144 |